Evaluating the transduction efficiency of systemically delivered AAV vectors in the rat nervous system - Yang, Olivia J.; Robilotto, Gabriella L.; Alom, Firoj; Alemán, Karla; Devulapally, Karthik; Morris, Abigail; Mickle, Aaron D. (Frontiers in Neuroscience, 2023)
Gene delivery or manipulation with viral vectors is a frequently used tool in basic neuroscience studies. Adeno-associated viruses (AAV) are the most widely used vectors due to their relative safety and long-term efficacy without causing overt immunological complications. Many AAV serotypes have been discovered and engineered that preferentially transduce different populations of neurons. However, efficient targeting of peripheral neurons remains challenging for many researchers, and evaluation of peripheral neuron transduction with AAVs in rats is limited. Here, we aimed to test the efficiency of systemic AAVs to transduce peripheral neurons in rats. We administered AAV9-tdTomato, AAV-PHP.S-tdTomato, or AAV-retro-GFP systemically to neonatal rats via intraperitoneal injection. After five weeks, we evaluated expression patterns in peripheral sensory, motor, and autonomic neurons. No significant difference between the serotypes in the transduction of sensory neurons was noted, and all serotypes were more efficient in transducing NF200+ neurons compared to smaller CGRP+ neurons. AAV-retro was more efficient at transducing motor neurons compared to other serotypes. Moreover, PHP.S was more efficient at transducing sympathetic neurons, and AAV-retro was more efficient at transducing parasympathetic neurons. These results indicate that specific AAV serotypes target peripheral neuron populations more efficiently than others in the neonatal rat.